Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Cumulative Review - Page 835: 28


$-2-6\sqrt 3$

Work Step by Step

$(\sqrt 3-4)(2\sqrt 3+2)$ =$\sqrt 3(2\sqrt 3+2)-4(2\sqrt 3+2)$ =$2(\sqrt 3)^{2}+2\sqrt 3-8\sqrt 3-8$ =$2(3)+(2-8)\sqrt 3-8$ =$6-6\sqrt 3-8$ =$6-8-6\sqrt 3$ =$-2-6\sqrt 3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.